(U+Th)-He evidence of Jurassic continuous hydrothermal activity in the Schwarzwald basement, Germany - Wernicke, Rolf Stephan; Lippolt, Hans J. (Chemical geology, 1997)
(U+Th)-He model and isochron ages of 21 botryoidal hematites collected from the Hohberg base-metal vein system in the Triberg granite complex, Mittelschwarzwald (Germany), cover most of the Jurassic period. The possibility of quantitative 4He loss triggered by successive hydrothermal events, although conceivable for individual hematites — based on a 4He retentivity study and calculated opening temperatures of hematite for 4He of >(90-180)°C — can largely be ruled out. Thus the range of model and isochron ages indicates that the majority of the hematites are not cogenetic. This is supported by a broad range of Pbtotal concentrations in the Hohberg botryoidal hematites (150-2700 ppm), by comparison with virtually identical Pbtotal concentrations found in cogenetic hematites from four different vein systems in the Schwarzwald. The Th/U ratios of the hematites vary by a factor of ∼700 (0.01-7.25) mainly as a result of the range of Th concentrations (0.1-74 ppm). The incorporation of substantial amounts of Th in hematite is thought to result from increased Th transport mobility, possibly caused by association with colloids and/or complexing in the ore solution. δ18O analyses of a ∼160 Ma old cogenetic hematite-quartz pair indicate that precipitation occurred from a fluid of magmatic origin at a temperature of ∼180°C. The regional temperature peak in the basement at the present erosional surface during the Jurassic (∼130°C) provides a lower temperature limit of hematite formation. This implies that hematite emplacement occurred at temperatures roughly ranging between ∼130 and ∼180°C. The Jurassic continuous hydrothermal activity suggests that the pre-rifting European craton is characterized by local thermal fluxes during a long time span.
Elektronische Reproduktion der Druck-Ausgabe vom 14. Juni 1998
Gesehen am 23.11.2022